Health advocacy in nursing: contribution to the reorientation of the Brazilian healthcare model - Maria Amélia de Campos Oliveira; Tharsila Martins Rios da Silva
ABSTRACT Inequalities are the result of the different positions held by individuals in different social spaces, and are related to the distribution of power and property. Health advocacy is a strategy to reduce such inequalities, especially those considered unfair and unnecessary, aiming to fully promote the right to health. This study aims to discuss the contribution of nursing in the field of health advocacy, which includes the right of everyone to a healthy life as one of the strategies for the reorientation of the Brazilian healthcare model.